1989
DOI: 10.1104/pp.89.4.1028
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of α-Tocopherol in Senescing Organs as Related to Chlorophyll Degradation

Abstract: a-Tocopherol (a-T) has been identified, using gas chromatography-mass spectroscopy and 'H-and 13C-nuclear magnetic resonance, in senescing leaves of Melia azedarach L. The content of a-T increased concomitantly with the breakdown of chlorophyll in senescing Vinca and Melia leaves. An increase in a-T was found also in detached Melia leaves, senescing in either light or darkness and in senescing, ethylene-treated orange leaves and fruit. The possibility that phytol, which is released from chlorophyll by chloroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
1
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 18 publications
3
65
1
3
Order By: Relevance
“…As each mole of chlorophyll contains one mole of esterified phytol, bulk chlorophyll degradation has long been proposed as the source of phytol for tocopherol biosynthesis in such green, photosynthetic tissues (Rise et al, 1989;Chrost et al, 1999;Valentin et al, 2006). The chlorophyll degradation pathway has recently been elucidated in Arabidopsis (Schelbert et al, 2009;Hörtensteiner and Kräutler, 2011;Hörtensteiner, 2013) (Figure 4C), and the phytol released from pheophytin a by pheophytinase could be esterified to fatty acids to yield fatty acid phytyl esters or phosphorylated by VTE5 and VTE6 to yield phytyl-DP (Valentin et al, 2006;Tanaka et al, 2010;DellaPenna and Mène-Saffrané, 2011;Lippold et al, 2012;Zhang et al, 2014;Vom Dorp et al, 2015) (Figure 4C).…”
Section: Discussionmentioning
confidence: 99%
“…As each mole of chlorophyll contains one mole of esterified phytol, bulk chlorophyll degradation has long been proposed as the source of phytol for tocopherol biosynthesis in such green, photosynthetic tissues (Rise et al, 1989;Chrost et al, 1999;Valentin et al, 2006). The chlorophyll degradation pathway has recently been elucidated in Arabidopsis (Schelbert et al, 2009;Hörtensteiner and Kräutler, 2011;Hörtensteiner, 2013) (Figure 4C), and the phytol released from pheophytin a by pheophytinase could be esterified to fatty acids to yield fatty acid phytyl esters or phosphorylated by VTE5 and VTE6 to yield phytyl-DP (Valentin et al, 2006;Tanaka et al, 2010;DellaPenna and Mène-Saffrané, 2011;Lippold et al, 2012;Zhang et al, 2014;Vom Dorp et al, 2015) (Figure 4C).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, transcription of stress-related genes is induced, resulting in the expression of enzymes involved in scavenging reactive oxygen species (9,10). The role of the stress-induced accumulation of specific lipids is only poorly understood (11)(12)(13). In contrast to galactolipids and phospholipids, which are abundant in plant membranes, different lipids (triacylglycerol, free fatty acids, and tocopherol) accumulate in the leaves during stress.…”
mentioning
confidence: 99%
“…Although our study provided insights into the effects of N sources and application rates on seed Toc in oilseed rape, our results pointed out a possible interaction between Toc and chlorophyll contents in plastids, and between Toc and N fertilizer sources and/or application rates. With the recent characterization of chlorophyll-derived phytol and phytyl phosphate kinase from Arabidopsis (Ischebeck et al, 2006;Valentin et al, 2006), it has been shown that the prenyl moiety of γ-Toc biosynthesis is derived from free phytol in seeds, indicating that phytol is recycled during chlorophyll breakdown (Peisker et al, 1989;Rise et al, 1989;Dörmann, 2007). Thus, the optimum plant growth caused by high N results initially in high photoassimilate storage in photosynthetic tissues and subsequently in efficient translocation to seeds.…”
mentioning
confidence: 99%